Gallstones and incident colorectal cancer in a large pan‐European cohort study. Issue 6 (11th January 2019) - Ward, Heather A; Murphy, Neil; Weiderpass, Elisabete; Leitzmann, Michael F; Aglago, Elom; Gunter, Marc J; Freisling, Heinz; Jenab, Mazda; Boutron‐Ruault, Marie‐Christine; Severi, Gianluca; Carbonnel, Franck; Kühn, Tilman; et al.
Abstract : Gallstones, a common gastrointestinal condition, can lead to several digestive complications and can result in inflammation. Risk factors for gallstones include obesity, diabetes, smoking and physical inactivity, all of which are known risk factors for colorectal cancer (CRC), as is inflammation. However, it is unclear whether gallstones are a risk factor for CRC. We examined the association between history of gallstones and CRC in the European Prospective Investigation into Cancer and Nutrition (EPIC) study, a prospective cohort of over half a million participants from ten European countries. History of gallstones was assessed at baseline using a self‐reported questionnaire. The analytic cohort included 334, 986 participants; a history of gallstones was reported by 3, 917 men and 19, 836 women, and incident CRC was diagnosed among 1, 832 men and 2, 178 women (mean follow‐up: 13.6 years). Hazard ratios (HR) and 95% confidence intervals (CI) for the association between gallstones and CRC were estimated using Cox proportional hazards regression models, stratified by sex, study centre and age at recruitment. The models were adjusted for body mass index, diabetes, alcohol intake and physical activity. A positive, marginally significant association was detected between gallstones and CRC among women in multivariable analyses (HR = 1.14, 95%CI 0.99–1.31, p = 0.077). The relationship between gallstones and CRC among men was inverse but not significant (HR = 0.81, 95%CI 0.63–1.04, p = 0.10). Additional adjustment for details of reproductive history or waist circumference yielded minimal changes to the observed associations. Further research is required to confirm the nature of the association between gallstones and CRC by sex. Abstract : What's new? Gallstones can be extremely painful. But might the inflammation they cause also increase the risk of colorectal cancer (CRC)? Previous results have been inconsistent. In this large, prospective study, the authors found a slight positive association between gallstones and CRC among women. For men, on the other hand, there was an inverse association, but the data didn't reach statistical significance. More research is needed to confirm and further explore these sex‐based differences.